Problem-based Interactive Physics E-Module in Physics Learning Through Blended PBL to Enhance Students' Critical Thinking Skills - Sujanem, R.; Putu Suwindra, I. N. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2023)
Problem-based interactive physics e-modules (Probinphys), accessed online, were chosen as an alternative method for enhancing high school students’ CTS. This study analyzed the efficacy of the Probinphys E-Module in enhancing high school students’ CTS and described student responses toward the Probinphys E-Module through the Blended-Problem Based Learning (blended-PBL) model. The Probinphys e-module was efficient in enhancing CTS if there was a significant enhancement in student CTS and the minimum average N-gain was in the moderate or consistent category. Student responses toward the Probinphys e-module were in the high category. This research applied one group pretest and posttest group design, involving 79 students in three groups from grade eleven. Before and after learning with the Probinphys E-Module, the three groups of students were given the same CTS test. The collected data were analyzed using Paired-Test, normalized gain (N-gain), and ANOVA. The results show that using the Probinphys e-module in blended PBL efficiently enhances students’ CTS, as indicated by the average N-gain for the three groups in the high category. The average N-gain is the same at 0.5 for the three groups or consistently. Student response toward the Probinphys e-module in blended-PBL is very high.